Editorial - Deniz Evcik (Archives of Rheumatology, 2010)
Dear readers of Turkish Journal of Rheumatology, It is a great pleasure to introduce this issue with 8 original articles, 3 case presentations and an invited review from Laure Gossec “Patient-Reported Outcomes in Rheumatoid Arthritis: Why are They Important and How Should They Be Assessed?” which most readers will find interesting and helpful. Nowadays exciting developments take place in rheumatoid arthritis classification criteria. American College of Rheumatology and European League Against Rheumatism Committees approved a new criteria set which focuses on identification of early arthritis. These criteria are the first revised form since the preliminary 1987 criteria. Surely the new criteria set will bring clinicians us new ideas both in management and treatment of rheumatoid arthritis. EULAR has established certain recommendations for the management of RA with synthetic and biological disease-modifying antirheumatic drugs and first announced in Rome during the congress. From this perspective, the Turkish League Against Rheumatism (TLAR) took necessary actions to put the guideline into practice in our country. I would like to inform that these recommendations will include both disease modifying antirheumatic drugs (synthetic and biologicals) and nonpharmacological treatments. The latter including wide range of rehabilitation approaches surely has an important role in the treatment process and needs appraisal by clinicians. Hereby, I would like to remind you the oncoming Annual Meeting of ACR to be held in Atlanta between 6-11 November. Best regards, Deniz Evcik, MD Editor